Ethnobotanical Survey of Medicinal Plants Used in Managing Hypertension in Warri South LGA, Delta State, Nigeria - Chijindu, Pass Chidiebere; Ogona, Mary Timeyin (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Cardiovascular disease, cataract, chronic kidney disease, heart failure and many other complications resulted from the effect of hypertension. Several communities especially the low-income earner rely more on traditional medicine because they are affordable and easily accessible. However, interest on medicinal plants is dwindling due to lack of knowledge on their usefulness. This study therefore was carried out to document the medicinal plants used in the management of hypertension in Warri South Local Government Area of Delta State. Semi-structured questionnaires were used to collect from 150 respondents among which are Herb Sellers and Herbal Practitioners. Twenty (20) plant species belonging to 17 families were identified for the management of hypertension with Persea americana being the highest mentioned plant having a relative frequency of citation of 0.33, followed by Allium sativum (0.29) and Vernonia amygdalina (0.22). Liliaceae, Zingiberaceae and Myrtaceae were the families with the highest number of plant species. The results obtained also showed that the leaves part of plant were the most frequently used while the decoction as a method of preparation had the highest percentage application in the management of hypertension. In conclusion, the role of different plants parts in the management of hypertension is vital to healthcare delivery. Hence, scientific validations and sustainable use of these plants are recommended so as to ensure their availability in the nearest future.